New Results for Periodic Solution of High-Order BAM Neural Networks with Continuously Distributed Delays and Impulses - Chang-Bo Yang; Ting-Zhu Huang; Jin-Liang Shao (Journal of Applied Mathematics)
By M-matrix theory, inequality techniques, and Lyapunov functional method, certain sufficient conditions are obtained to ensure the existence, uniqueness, and global exponential stability of periodic solution for a new type of high-order BAM neural networks with continuously distributed delays and impulses. These novel conditions extend and improve some previously known results in the literature. Finally, an illustrative example and its numerical simulation are given to show the feasibility and correctness of the derived criteria.